Sterols of Glaucocystophytes - Leblond, Jeffrey D.; Timofte, Hermina Ilea; Roche, Shannon A.; Porter, Nicole M. (Phycological research, 2011)
SUMMARY Glaucocystophytes are a group of evolutionarily important freshwater algae that have an almost intact cyanobacterium, referred to as a cyanelle, as the photosynthetic organelle. Because of this, they have been the subject of a large number of studies over the past few decades on how a cyanobacterium transitioned into a chloroplast. However, studies on their lipid composition have lagged behind those on other areas of glaucocystophyte cell biology. To this end, we have examined the sterol composition of Cyanophora paradoxa Korshikov and Glaucocystis nostochinearum Itzigsohn in order to identify sterols left unidentified in previous studies. We have found that two isolates of G. nostochinearum and one of C. paradoxa uniformly produced three sterols: 24‐methylcholest‐5‐en‐3β‐ol, 24‐ethylcholesta‐5,22E‐dien‐3β‐ol, and 24‐ethylcholest‐5‐en‐3β‐ol.